Comparative Evaluation of Mechanical Properties of Clear Aligner Biosheet Materials -An In Vitro Study - Pallavi Kusum; Shantanu Sharma; Sovendu Jha (Journal of Pharmacy and Bioallied Sciences)
Background: Thermoplastic polymers are extensively used in the fabrication of clear aligners due to their biocompatibility, flexibility, and mechanical properties. Evaluating the mechanical performance of these materials under clinical conditions is crucial for optimizing their application. Materials and Methods: Two types of thermoplastic polymers, **Duran** and **Zendura**, were selected for analysis. Specimens with uniform dimensions (10 mm × 50 mm × 1 mm) were prepared from sheets of each material. Tensile strength, elastic modulus, and flexural strength were measured using a universal testing machine (UTM) under controlled conditions. Cyclic loading tests were conducted to simulate intraoral forces over 1000 cycles at 37°C in an artificial saliva solution. Data were statistically analyzed using one-way ANOVA with a significance level of P < 0.05. Results: Zendura exhibited higher tensile strength (average: 62 ± 3 MPa) and elastic modulus (average: 2400 ± 100 MPa) compared to Duran (tensile strength: 55 ± 2 MPa; elastic modulus: 2100 ± 90 MPa). Similarly, Zendura showed superior flexural strength. Cyclic loading tests revealed that Zendura retained 96% of its original mechanical properties after 1000 cycles, while Duran retained 93%. Conclusion: Zendura outperformed Duran in tensile strength, elastic modulus, and flexural strength, making it a highly suitable material for aligner fabrication. However, Duran demonstrated satisfactory flexibility and durability, which may provide specific clinical advantages.